THE CULTURAL IDENTITIES OF FOREIGN LANGUAGE TEACHERS - Heri Santoso (Universitas Galuh, 2021)
ABSTRACTMany foreign language teachers, especially English teachers, come from various regions. With their abilities, they managed to compete to be teaching staff in the capital city. Based on their ability to teach foreign languages, all of this cannot be separated from the cultural identity they carry in the world of education and, of course, will carry over to the classroom where they teach. This study uses an online platform because it is impossible to meet face to face. In each question contains a cultural identity whose use can affect the way they teach foreign languages. This cultural identity often draws attention to where they come from, their nature, how they think, and how they speak up, accompanied by their language teaching skills. Besides that, we will also find the advantages and disadvantages of the cultural identity they carry. The results showed that foreign language teachers in English learning has a cultural identity to teach in the classroom. Keywords: foreign language teachers, cultural identity, English teachers, language teaching